2018
DOI: 10.2166/ws.2018.055
|View full text |Cite
|
Sign up to set email alerts
|

Study of the variation of haloacetic acids in a simulated water distribution network

Abstract: This paper presents the analysis of the variation of haloacetic acids (HAAs) for different pipe materials in a distribution system. The work involved an experimental study on a simulated distribution system assembled in the Hydraulic Laboratory of the Engineering Institute at the National Autonomous University of Mexico (Instituto de Ingeniería UNAM). Two different scenarios were investigated based on different pipe materials, variation of temperature and initial chlorine concentrations (4.0 and 4.5 mg/L). Fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…DBP exceedances occur more often in small systems, which have fewer resources for treatment to reduce DBP levels, such as filtering organic matter prior to disinfection [ 51 ]. DBP formation in the distribution system may be higher with polyethylene pipes [ 52 ] and with increasing diameter and pipe age [ 53 ].…”
Section: Contaminant Profilesmentioning
confidence: 99%
“…DBP exceedances occur more often in small systems, which have fewer resources for treatment to reduce DBP levels, such as filtering organic matter prior to disinfection [ 51 ]. DBP formation in the distribution system may be higher with polyethylene pipes [ 52 ] and with increasing diameter and pipe age [ 53 ].…”
Section: Contaminant Profilesmentioning
confidence: 99%
“…Chloramine has now become a frequently used disinfectant to reduce the formation of regulated disinfection byproducts (DBPs) such as trihalomethanes (THMs) and haloacetic acids (HAAs) [ 23 ]. However, the interactions between chloramine and the dissolved organic compounds in water results in the formation of nitrogen-disinfection byproducts (N-DBPs) [ 24 , 25 ], which are often more toxic than THAs and HAAs [ 26 , 27 , 28 , 29 , 30 , 31 ]. Previous studies have found that antibiotics can be transformed into N-DBPs by reacting with the disinfectant chloramine; for example, metronidazole could be oxidized by monochloramine disinfectant to form dicholoacetamide (DCAcAm) [ 32 ] and oxytetracycline could form the N-nitrosodimethylamine (NDMA) [ 33 ], which have been cited as research priorities by the U. S. EPA owing to their greater cytotoxicity and genotoxicity than currently regulated C-DBPs (e.g., THMs) [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Düzenli olarak küçük miktarlarda maruz kalınan dezenfeksiyon yan ürünlerinin insan sağlığına olumsuz etkileri vardır [10]. THM grubunda kloroform, klorodiborometan, bromodiklorometan ve bromoform bileşiklerinin, HAA gurubundan monokloroasetik asit, dikloroasetik asit, trikoloroasetik asit, monobromoasetik asit, dibromoasetik asit bileşiklerinin kanser, sitotoksik, genotoksik, üreme anomalileri, doğum kusurlar, böbrek ve karaciğer hasarı, sinir sistemi hasarı gibi sağlık etkileri ortaya çıkardığı bildirilmiştir [11][12][13][14].…”
Section: Introductionunclassified